UNJUK KERJA MODIFIKASI SBR AEROB TERHADAP PENYISIHAN COD - Junaidi, Junaidi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Sequencing  Batch  Reactor  (SBR)  is  a  modification  process  from  activated  sludge  that has flexibility in its implementation. In aerobic SBR, all phase is in aerobic cycles those are filling phase, reaction  phase,  settling  phase,  drawing  phase  and  idle  phase.  In  this  research,  idle phase  is modified  as  stabilize  phase  where  biomass  is  aerated  for  finite  time  so  sorption capacity    of biomass  back  to  normal  This  research  shows  that  optimum  COD  removal  is achieved  in  one  hour reaction  time  and  stabilization  time  is  6  which  is  97,02  %  using  active carbon and  95,23 % without active carbon. In conclusion, COD removal capabilities with GAC is better than without GAC.